Resolution of Mass Effect and Compression Symptoms following Endoluminal Flow Diversion for the Treatment of Intracranial Aneurysms - Szikora, I. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Alleviation of aneurysm induced mass effect has been difficult with both conventional endovascular and surgical techniques. Our aim was to study the efficacy of endovascular flow modification on aneurysm-induced mass effect and compression syndrome, as demonstrated by cross-sectional imaging studies and clinical follow-up. MATERIALS AND METHODS: Thirty aneurysms larger than 10 mm were treated by flow diversion alone and previously had undergone pre- and posttreatment cross-sectional imaging. Pretreatment MR imaging or contrast CT, follow-up angiography at 6 months, and follow-up MR imaging studies between 6 and 18 months were retrospectively analyzed. The neurologic and neuro-ophthalmologic statuses of all patients were recorded before treatment and at the time of follow-up cross-sectional imaging. RESULTS: At 6 months, 28 aneurysms were completely occluded, 1 had a neck remnant, and 1 had residual filling on angiography. Between 6 and 18 months, 3 aneurysms decreased in size and 27 completely collapsed as demonstrated on MR imaging. Before treatment, 6 patients had vision loss, 10 had double vision due to a third or sixth nerve palsy or both, and 1 had hemiparesis due to brain stem compression. On MR imaging follow-up, vision loss had either improved or resolved in all except 1 patient, double vision had resolved completely (7/10) or partially (3/10), and the patient with brain stem compression became asymptomatic. There was no bleeding observed in this series. One parent artery thrombosis resulted in a major infarct. CONCLUSIONS: Endovascular flow diversion is a highly effective technique for resolving radiologic mass effect and clinical compression syndromes.